Identification of Marker Molecules in Aqueous Plant Extracts Affecting the Gold Nanostructures’ Morphology and Size - Elgaleidh, Mareia Ahmed-M; Dilek Tepe, Hafize; Doyuk, Fatma; Çeter, Talip; Yazgan, İdris (Wiley, 2024)
AbstractThis work was performed as a comparative study using nine different aqueous pollen grain extracts from eight different genera (Juniperus, Biota, Cupressus, Abies, Pinus, Cedrus, Populus and Corylus) to synthesize gold nanostructures (AuNSs) to understand if there is any possible marker that helps to predict the final morphology and size of the AuNSs. Principal component analysis (PCA) revealed that Apigenin and Pinoresinol compounds are the marker molecules in determination of the AuNSs physical characteristics while total protein, reducing carbohydrate, flavonoid and phenol contents did not show any statistically meaningful outcome. The “dominancy hypothesis” was tested by paying attention to the most concentrated phenolic acids and flavonoids in the control of AuNSs morphology and size, for which correlation analysis were performed. The statistical findings were tested using two new more pollen extracts to validate the models. Three main findings of the study were (i) determination of Apigenin and Pinoresinol levels in pollen extract can give an insight into the AuNSs physical characters, (ii) the most concentrated phenolic acids and flavonoids don't need to be same to pose same dictative effect on AuNSs morphology and size, rather relatively abundant ones in the extract play the key role and (iii) differences in the polymeric structures (e. g. lignin, cellulosic compounds etc.) have minor effect on the final morphology and size of the AuNSs.
Keywords: Flavonoids; Plant Extracts; Water; Antioxidants; Lignans; Nanostructures; Hydroxybenzoates; Gold; Apigenin; Furans